Legality of surrogacy in Indonesia based on transcendental values - Rizka, Rizka; Ab Rahman, Rozanah (Barking London, 2020)
Surrogacy practice, where a woman gives birth to another woman’s child, is one of the most controversial procedures in the field of assisted reproduction. There are various intentions of surrogacy, and it has been practiced around the world for a long time. This paper aims to discover the legality of surrogacy under the law existed and enforced in Indonesia that govern the activities of surrogacy. There are several countries acknowledging the agreement between surrogate mothers and the genetic parents. Accordingly, a law based on transcendental values is needed in Indonesia in an effort to regulate the surrogacy practice which would possibly give rise to issues of nasab (genealogy), guardian and inheritance.